Bankruptcy Analysis of Transportation Companies Listed on the Indonesian Sharia Stock Index (ISSI) Using the Springate and Grover Method Before and During the Pandemic Covid-19 - Kurniawan, Indra (University of Darussalam Gontor, 2024)
This research aims to compare the Springate and Grover bankruptcy models, evaluating their accuracy in predicting bankruptcies among transportation sector companies listed on the Indonesian Sharia Stock Index (ISSI) before and during Covid-19 (2018-2021). Conducted as quantitative research, the study utilizes secondary financial report data. Findings reveal significant differences between the two models, with the Grover method demonstrating higher accuracy in predicting bankruptcy among transportation sector companies on ISSI before and during the pandemic. Keywords: Bankruptcy, Springate, Grover, Financial Reports.